Olfactory Virtual Reality (OVR) for Wellbeing and Reduction of Stress, Anxiety and Pain - Tomasi, David; Ferris, Hannah; Booraem, Priscilla; Enman, Lindsay; Gates, Sheri; Reyns, Emily (Jour Med Resh and Health Sci, 2021)
Background: As part of a consistent effort to examine and provide integrative medical approaches to the therapeutic offering for psychophysical health, this study investigates the utilization of Olfactory Virtual Reality (OVR) in an inpatient psychiatry unit, more specifically in the Shepardson 3 Inpatient Psychiatry Unit at the University of Vermont Medical Center, in Burlington, VT, USA. Objectives: The purpose of this protocol is to explore the therapeutic value of olfactory virtual reality (OVR) in the above described population, and to collect statistically significant data to determine the feasibility of potential future OVR studies. Method: Direct subject observation and monitoring in the context of Olfactory Virtual Reality (OVR) sessions and Qualitative data collection via the administration of subject surveys, subdivided in: a) Pre-OVR experience, b) Immediate post-OVR experience, and c) 1-to-3-hour post-OVR experience questionnaires. Results: The research yielded positive outcomes in all areas investigated, despite challenges related to the utilization of the device itself, issues in individual olfactory threshold, and COVID-19 restrictions and limitations. Conclusion: The outcome of this study indicates that the utilization of olfactory virtual reality technologies is a safe and effective integrative approach to target several aspects of psychological and physical health such as anxiety, stress, and pain, in combination with the psychotherapeutic and pharmacological standards of care in inpatient psychiatry.